Faktum, Faktizität, Wirklichkeit Phänomenologische Perspektiven (Felix Meiner Verlag, 2023)
The research volume contains contributions from phenomenological research that deal with questions of fact, facticity, reality and the real. What concept of the real or reality, for example, is phenomenology able to develop, and how can it take a stand on the criticism that has been levelled at it in recent times by the "new realism"? Such questions are discussed with special attention to the natural, social and political as well as the technical implications of a phenomenological concept of reality.